Development of the SIP (Smart Inclusive School) Web-Based E-Learning Platform for Empowering Teachers and Parents at RA Zidni ‘Ilma Sukoharjo: Pengembangan Platform E-learning SIP (Sekolah Inklusif Pintar) Berbasis Web untuk Pemberdayaan Guru dan Orang Tua di Sekolah RA Zidni ‘Ilma Sukoharjo - Muqorobin; Sumadi; Tira Nur Fitria (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this community service activity is to introduce and train the use of the web-based SIP (Smart Inclusive School) e-learning platform (https://zidni-sip.web.id/elearning) that can empower teachers and parents at RA Zidni 'Ilma Sukoharjo to be able to create, manage, and deliver digital-based learning materials effectively. The method used in this community service activity is direct material presentation and direct practice. The program was implemented in July–August 2025 through ten stages, starting from needs analysis, e-learning introduction training, material creation, content publication, and evaluation. Teachers were trained to create interactive materials and manage the system, while parents were able to integrate their children's learning process. Evaluation results from Google Forms showed the success of the program. Teachers and parents were able to utilize the platform independently, increase engagement, and support inclusive education. Based on a questionnaire from 28 respondents, the activity was rated very good (average 4.89/5), especially in terms of benefits and implementation. Participants hoped for further training and feature development to optimize the use of technology.